Digital Marketing Strategies Adopted by the FMCG Sector: A Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the role of digital marketing in influencing consumer behaviour within the Fast-Moving Consumer Goods (FMCG) sector. With the rapid advancement of technology and increased internet penetration, digital platforms have become a significant medium for promoting FMCG products. The purpose of this research is to understand how digital marketing strategies impact consumer awareness and purchasing decisions. The study adopts a descriptive research design, utilising both primary and secondary data. Primary data is collected through structured questionnaires from respondents, while secondary data is gathered from journals, websites, and industry reports. The findings indicate that digital marketing significantly enhances brand visibility, customer engagement, and purchase intention, particularly among younger consumers. The study contributes to existing literature by focusing specifically on the effectiveness of digital marketing in the FMCG sector and highlighting consumer perceptions. It provides valuable insights for marketers aiming to optimise digital strategies.